2021
DOI: 10.3389/fonc.2021.630136
|View full text |Cite
|
Sign up to set email alerts
|

Immune-Related Adverse Events Are Associated With Clinical Benefit in Patients With Non-Small-Cell Lung Cancer Treated With Immunotherapy Plus Chemotherapy: A Retrospective Study

Abstract: BackgroundThe immunotherapy plus chemotherapy combination is one of the most promising treatments in advanced non-small-cell lung cancer (NSCLC). Immunotherapy often causes immune-related adverse events (irAEs), which have been reported to be associated with the good clinical outcomes. However, the effects of immunotherapy plus chemotherapy remain unknown. In this study, we investigated the association between irAEs caused by immunotherapy plus chemotherapy and clinical efficacy in patients with advanced NSCLC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 29 publications
1
10
2
1
Order By: Relevance
“…We also found that individuals who developed IMC had improved survival outcomes when compared to those who did not develop IMC, including in a landmark sensitivity analysis, which is concordant with previously published literature [43][44][45][46][47][48] . However, PRS UC and PRS CD were not associated with PFS or OS, suggesting that the genetic basis of autoimmune disease susceptibility is distinct from genetic factors influencing survival outcomes.…”
Section: Discussionsupporting
confidence: 90%
“…We also found that individuals who developed IMC had improved survival outcomes when compared to those who did not develop IMC, including in a landmark sensitivity analysis, which is concordant with previously published literature [43][44][45][46][47][48] . However, PRS UC and PRS CD were not associated with PFS or OS, suggesting that the genetic basis of autoimmune disease susceptibility is distinct from genetic factors influencing survival outcomes.…”
Section: Discussionsupporting
confidence: 90%
“…To our knowledge, the present study is the first to demonstrate this by combining rigorous ITB control using landmark ( Tables 3 , 4 ) and time-dependent analyses ( Supplementary Table 5 ), with multivariable testing that includes all currently established survival predictors, both laboratory (PD-L1 TPS, NLR) and clinical (treatment type, treatment line, ECOG PS, Table 4 and Supplementary Table 5 ). Furthermore, particularly relevant for the contemporary practice is the inclusion of a large chemoimmunotherapy subcohort (n > 250, Table 1 ) in this analysis, which is the predominant therapeutic strategy for most NSCLC patients currently ( 3 , 4 ), in contrast to previous studies who have analyzed IO-monotherapy ( 41 , 50 ) or small chemoimmunotherapy series with less than 100 patients ( 51 ). Our results show that the relationship between occurrence of irAEs and ICI efficacy is very strong (HR = 0.4, Table 4 ), stronger than that of PD-L1 TPS or NLR, and that it persists regardless of concurrent or previous chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…The literatures that could be evaluated after screening were all duplicated with those previously screened. Finally, a total of 11 studies (Figure 2) were included in the systematic review (11)(12)(13)15,(41)(42)(43)(44)(45)(46)(47). The study was conducted by 3 people to extract data, statistical survival data, and perform statistical analysis.…”
Section: Resultsmentioning
confidence: 99%